2008
DOI: 10.1097/01.hcm.0000318755.24332.4b
|View full text |Cite
|
Sign up to set email alerts
|

Employee Satisfaction and Employee Retention

Abstract: Over the last few years, most health care facilities have become intensely aware of the need to increase patient satisfaction. However, with today's more consumer-driven market, this can be a daunting task for even the most experienced health care manager. Recent studies indicate that focusing on employee satisfaction and subsequent employee retention may be strong catalysts to patient satisfaction. This study offers a review of how employee satisfaction and retention correlate with patient satisfaction and al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 4 publications
1
14
0
Order By: Relevance
“…; Collins et al. ). Currently, FLW occupations are among the fastest growing in the United States; collectively, their projected growth rate is higher than the growth rate of all health and health care occupations in the U.S. workforce (Bureau of Labor Statistics ).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Collins et al. ). Currently, FLW occupations are among the fastest growing in the United States; collectively, their projected growth rate is higher than the growth rate of all health and health care occupations in the U.S. workforce (Bureau of Labor Statistics ).…”
Section: Discussionmentioning
confidence: 98%
“…Frontline health care workers play a critical role in the delivery of basic health care services and have an important impact on patient satisfaction and other health care outcomes (Schindel et al 2006;Collins et al 2008). Currently, FLW occupations are among the fastest growing in the United States; collectively, their projected growth rate is higher than the growth rate of all health and health care occupations in the U.S. workforce (Bureau of Labor Statistics 2004).…”
Section: Discussionmentioning
confidence: 99%
“…[2,3] Evidence suggests that when healthcare professionals are engaged in their health system, organizations benefit from reductions in mortality, adverse drug events, errors, and infection rates,[5–8] as well as enhanced quality of care and patient experience. [7,9,10] Findings from a large-scale study in the NHS indicated that trusts with higher staff engagement exhibit better financial performance. [7] Alongside this growing evidence for the link between engagement and performance, there have been a number of advances in physician[3,6,11,12] and patient engagement in healthcare,[1315] Efforts to engage the spectrum professionals and stakeholders who design and carry out quality improvement initiatives, however—a process outlined within numerous healthcare improvement models.…”
Section: Introductionmentioning
confidence: 99%
“…More effort has then been undertaken to understand the work experiences of nurses. This has involved issues such as workload (Aiken,31 The Effects of Personal and Organizational Resources on Work and Well-Being Outcomes among Turkish Nurses Clarke, Sloan, Sochalski & Silber, 2002), overtime work, patient abuse of nurses, lack of adequate resources, hospital restructurings and how these experiences influence nurse satisfaction, burnout (Greenglass, Burke & Fiksenbaum, 2001;Leiter & Maslach, 2001), absenteeism, intent to leave the profession (Lowe, 2012;Collins, Collins McKinnies & Jensen, 2008;Mannion, Davies, & Marshall, 2005) and quality of patient care (Aiken, 2002: Vahey, Aiken, Sloane, Clarke & Vargas, 2004.…”
Section: Introductionmentioning
confidence: 99%